Safety professionals handbook - Haight, Joel M. (American Society of Safety Professionals, 2022)
"A comprehensive text for occupational safety and health professionals, the Safety Professionals Handbook covers many areas in the safety and health fields as well as in the environmental fields. Sections include Process Safety Management; Risk Management; Traditional Safety Management; Health and Safety Management Systems; Safety Engineering; Ergonomics and Human Factors Engineering; Fire Protection Engineering; Industrial Hygiene and Occupational Health; Environmental Engineering; Engineering Management; Leadership, Organization, and Culture; and Global Safety and Health and Sustainability"--